A novel approach for the fabrication of low-stress bimorph RF-MEMS switches. Issue 1 (12th June 2017) - Sharma, Hitesh Kumar; Rani, Shalu
Abstract : Purpose: The purpose of this paper is to design a low-cost stress bimorph RF-MEMS switch which is the desired transmission area application. Design/methodology/approach: The bimorph structure of the low-temperature plasma-enhanced chemical vapor deposition (PECVD) of thermal oxide and gold are utilized to create the vibrating membrane. The effects of process conditions of low-temperature oxide deposited using the PECVD technique enable stress-free deposition of the key structural layer. Findings: Scanning electron microscope images of the RF micro-switch confirms negligible stress in the released structure. The RF performances of this device exhibit isolation around 43 dB of up to 50 GHz in the OFF-state position and an insertion loss of less than 0.18 dB in the ON-state. Originality/value: The finite element method results show good isolation of 43 dB and less insertion loss of 0.18 dB.